Modeling and simulation of hybrid electric propulsion systems for amphibious vehicle - Nguyen, Van-Tong Em; Nguyen, Van-Trang; Le, Tat-Hien; Ninh, Cao-Thanh Nhi; Vo, Thai-Nguyen (Sound & Vibration, 2026)
Amphibious vehicles operate across land and water, requiring stable environmental transitions. Although series hybrid electric propulsion systems (Series HEPS) offer flexible power distribution for these dual-environment demands, existing studies often limit dynamic analysis to individual environments. The transition phase, where buoyancy, hydrodynamic drag, and wheel loads vary simultaneously, lacks a unified mathematical framework. This study develops an integrated longitudinal dynamic model coupled with a Series HEPS, enabling continuous simulation across three phases: land, water, and transition. The land phase considers rolling resistance, aerodynamic drag, and wheel traction, whereas the water phase determines hydrodynamic resistance via the Holtrop-Mennen method and a propeller thrust model. Notably, for the transition phase, a proposed geometric relationship links longitudinal displacement along the bank slope to submergence depth, determining real-time buoyancy variations and wheel load redistribution. Simulation scenarios evaluate velocity, acceleration, and traction requirements across all phases, analyzing the influence of bank slope angles and ground friction on climbing capability. Simulation results demonstrate that the proposed HEPS configuration is highly reliable, achieving maximum speeds of 60 km/h on land and over 8 km/h in water. The system effectively satisfies the dynamic performance requirements, including velocity, acceleration, and gradeability, across the terrestrial, aquatic, and transitional phases. The simulation results indicate that the proposed HEPS configuration provides continuous tractive effort across the operating phases, achieving the required on-road design speed of 60 km/h, reaching approximately 8.7 km/h in calm-water operation, and attaining terminal transition velocities of approximately 7.2–9.5 km/h during the aquatic-to-terrestrial transition. This framework provides a useful analytical tool for the preliminary design and dynamic evaluation of hybrid amphibious vehicles.